Zinc-catalyzed hydroamination: a review - Sengupta, Manideepa; Queffelec, Clemence; Rodriguez-Zubiri, Mireia (ACS Catalysis, 2026)
The hydroamination reaction, defined as the direct addition of an N-H bond across unsaturated carbon-carbon bonds, provides a direct route to substituted amines. These amines are indispensable building blocks in nitrogen-containing heterocycles, which are central to pharmaceuticals, agrochemicals, and fine chemicals. Unlike conventional multistep processes, hydroamination enables streamlined and sustainable access to diverse organo-nitrogen frameworks. Within this context, zinc-catalyzed intra- and intermolecular hydroaminations have emerged as particularly attractive due to zinc's abundance, low toxicity, wide availability, and its ability to enable efficient catalytic processes with reduced environmental impact. Zinc catalysts operate under mild, environmentally benign conditions, displaying broad substrate compatibility and potential for enantioselective control through coordination with chiral ligands. This review highlights the progress made in zinc-catalyzed hydroamination, encompassing homogeneous and heterogeneous systems, structure-activity relationships, mechanistic insights, and emerging applications. Particular attention is given to the advantages of zinc catalysis in organic synthesis and its relevance to industrial-scale transformations.
Keywords: emerging applications; heterogeneous; homogeneous; hydroamination; mechanisms; structure-activityrelationship; zinc